Healthcare resource utilization and costs in individuals with Huntington's disease by disease stage in a US population. (31st December 2022) - Exuzides, Alex; To, Tu My; Abbass, Ibrahim M.; Ta, Jamie T.; Patel, Anisha M.; Surinach, Andy; Fuller, Rebecca L. M.; Luo, Jia
Abstract: Aims: To quantify healthcare resource utilization (HRU) and costs by disease stage in individuals with Huntington's disease (HD) in a US population. Materials and methods: This retrospective cohort study used administrative claims data from the IBM MarketScan Commercial, Multi-State Medicaid, and Medicare Supplemental Databases between 1 January 2009 and 31 December 2018. Individuals with an HD claim between 1 January 2010 and 31 December 2017 were selected. Index date was the date of first HD diagnosis. Individuals were required to have continuous enrollment for ≥ 12 months pre-index, 3 months post-index, and have no pre-index HD claims. All-cause HRU and costs per patient per month (PPPM) (overall and stratified by disease stage) were assessed for individuals with HD. Results: A total of 2, 669 individuals with HD were identified. Of these, 1, 432 (53.7%), 689 (25.8%), and 548 (20.5%) had early-, middle-, and late-stage HD at baseline, respectively. Mean HRU PPPM by post-index HD stage increased with disease stage for outpatient visits, pharmacy claims, and HD-related pharmacy claims ( p  < 0.05 for all). Mean inpatient visits and emergency room visits PPPM were highest in individuals with middle-stage HD ( p  <0.05 for all). Mean total all-cause healthcare cost PPPM for individuals with HD was $2, 889, and it was significantly higher in middle-stage individuals, at $7, 988, compared with early- and late-stage individuals, at $3, 726 and $5, 125, respectively; p  <0.0001. Limitations: In the absence of disease staging information in administrative claims data, staging was based on the presence of clinical markers in claims. Our evaluations didn't include the indirect costs of HD, which may be substantial as HD typically affects people at their peak earning potential. Conclusions: HRU and costs of care are high among individuals with HD, particularly among those with middle- and late-stage disease. This indicates that the disease burden in HD increases with disease stage, highlighting the need for interventions that can slow or prevent disease progression.